2022
DOI: 10.3390/risks10100185
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, Firm Performance and Financial Leverage across Developed and Emerging Economies

Abstract: This research inquiry analyzed the association between corporate governance and firm performance through the mediating role of financial leverage based on panel data of 2568 firms during the period from 2002 to 2017. The study uses a two-step dynamic panel as well as a generalized method of moments (GMM) to estimate these relationships. The findings demonstrated financial leverage mediates the relationship between corporate governance and firm performance in the context of developed economies, and also in emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 112 publications
1
10
0
1
Order By: Relevance
“…At the same time, the board of directors leads to better control of sustainability reporting (Alipour, 2013) and encourages companies to disclose more environmental practices (Katmon et al , 2019). Prior literature on board governance has shown that board size influences sustainability reporting practice (Chau and Gray, 2010; Shamil et al , 2014; Erin et al , 2016), and that a large board size tends to be more effective, as they are less likely to be influenced by management or external forces (Adams, 2013; Dienes and Velte, 2016; Erin et al , 2022; Kijkasiwat et al , 2022). However, some scholars (Ntim and Soobaroyen, 2013; Shamil et al , 2014) argue the opposite that boards with smaller boards are more efficient.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…At the same time, the board of directors leads to better control of sustainability reporting (Alipour, 2013) and encourages companies to disclose more environmental practices (Katmon et al , 2019). Prior literature on board governance has shown that board size influences sustainability reporting practice (Chau and Gray, 2010; Shamil et al , 2014; Erin et al , 2016), and that a large board size tends to be more effective, as they are less likely to be influenced by management or external forces (Adams, 2013; Dienes and Velte, 2016; Erin et al , 2022; Kijkasiwat et al , 2022). However, some scholars (Ntim and Soobaroyen, 2013; Shamil et al , 2014) argue the opposite that boards with smaller boards are more efficient.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Одной из важных проблем количественного исследования эффективности практик корпоративного управления является выбор конкретных показателей и переменных для анализа [9].…”
Section: экономические наукиunclassified
“…One commonly used metric to assess a company's FP. Another important aspect of FP is the liquidity of the firm, which refers to its ability to meet short‐term financial obligations (Kijkasiwat et al, 2022). Larger firms often have greater access to credit and capital markets, which can provide greater flexibility in managing their liquidity and working capital needs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To avoid the risks of large corporate scandals, corruption, financial crises, fraudulent activity, and corporate failures, firms and countries adopted strong CG practices (Karamoy & Tulung, 2020). Organizations should follow well‐defined CG practices for effectively managing firm processes, providing opportunities for firm growth, better access to resources, and surviving in market competition, which will foster firm performance (Kijkasiwat et al, 2022). Economic growth in China has accelerated during the past 3 years due to economic reforms in the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation